Influence of sorghum flour addition on flat bread in vitro starch digestibility, antioxidant capacity and consumer acceptability - Yousif, A.; Nhepera, Dorothy; Johnson, Stuart (Elsevier, 2012)
Wheat flour (WF) flat bread was prepared with varying levels of wholegrain ‘‘white’’ sorghum flour (WSF) or ‘‘red’’ sorghum flour (RSF). Farinograph dough rheology indicated reduced water absorption and stability time and increased breakdown with increased sorghum flour addition. The total phenolic content and antioxidant capacity of the 40% RSF flat bread >40% WSF flat bread > control (100% WF) flat bread. The rapidly digestible starch (RDS) level was lower in the 40% WSF and 40% RSF flat breads than the control (100% WF). Hedonic sensory evaluation indicated that sorghum addition did not reduce the sensory preference for the flat breads. Human clinical studies are now required to determine if the lower levels of RDS and higher antioxidants observed in the sorghum containing flat breads translate into beneficial low glycemic index and reduced oxidative stress in vivo.